PENGARUH MODEL PEMBELAJARAN PAKEM BERBASIS MULTIMEDIA TERHADAP HASIL BELAJAR TEMATIK - Lubis, Rut Inriani Ruspita; Purba, Nancy Angelia; Siregar, Junifer (Jurnal Ilmiah Aquinas, 2023)
The purpose of this study is to find out how much influence the multimedia-based standard learning model has on thematic learning outcomes in the sub-themes of work around me. This type of research is a quasi-experimental. Experimental research is to use the research method used to find the effect of treatment on others under controlled conditions which was carried out at UPDT SD Negeri 122371 Pematang Siantar with a saturated sample of 30 students. The procedure for the steps in the study was carried out by giving a pretest and giving treatment to the class that was the subject of the study using a multimedia-based standard learning model. The results obtained that the use of the standard model has a positive effect on student learning outcomes in social studies, science and Indonesian lessons as evidenced by the results of the hypothesis testing that has been carried out, it is obtained that tcount is 13.62 and ttable is 2,048, tcount>ttable = 13.62>2.040, The difference between the results of the pretest and posttest is significant and it can be concluded that H0 is rejected and Ha is accepted, so the hypothesis in this study is accepted. Students become more active and enthusiastic in the learning process by using learning media compared to the teaching and learning process without using learning media. Keywords: PAKEM Model, Student Learning Outcomes.